GESTATIONAL DIABETES MELLITUS AFTER ART AND IN SPONTANEOUS PREGNANCY: DOES THE METHOD OF CONCEPTION MATTER IN THE IMPLEMENTATION OF OBSTETRIC AND PERINATAL COMPLICATIONS? - Мурзин, Александр Викторович; Мелкозерова, Оксана Александровна; Дерябина, Елена Геннадьевна (Mother and Baby in Kuzbass, 2023)
Recent studies have shown that pregnancy resulting from the use of assisted reproductive technologies (ART) is associated with an increased risk of developing gestational diabetes mellitus (GDM). At the same time, GDM is an independent risk factor for a number of obstetric and perinatal complications. Does the method of conception matter in realizing the synergy of ART and GDM risk factors?Purpose of the study – to study the role of assisted reproductive technologies in the development of obstetric and perinatal complications in patients with gestational diabetes mellitus.Material and methods. An observational single-center retrospective cohort continuous study was carried out, the main group (n = 41) consisted of patients with pregnancy resulting from the use of ART, complicated by the development of GDM. The comparison group (n = 35) included patients with spontaneous pregnancy complicated by the development of GDM. The analysis of somatic and gynecological anamnesis, reproductive function was carried out, as well as perinatal complications and pregnancy outcomes in the study groups were analyzed.Results. Patients with post-ART pregnancies complicated by GDM were significantly older than those with spontaneous pregnancies complicated by GDM (37 [34;40] years versus 27 [24;36] years); p = 0.00), their obstetric-gynecological history was significantly more often burdened (95.1 % (39/41) vs 45.7 % (16/35); p=0.000), they more often suffered from hypothyroidism (OR 5.325; 1.080–26.241; p = 0.031) and chronic diseases of the urinary system (OR 21.760; 2.704–175.09; p = 0.000). Prolonged use of progesterone preparations beyond 22 weeks of gestation (OR 11.917; 4.038–35.168; p = 0.000) is statistically significantly associated with the risk of GDM in patients after ART. Pregnancy resulting from ART and proceeding against the background of GDM significantly more often than spontaneous pregnancy with GDM was complicated by the development of moderate preeclampsia (OR 4.641; 0.930-23.158; p = 0.055), permanent threat of abortion (OR 3.529; 1.350–9.228 ; p = 0.009), the formation of fetal macrosomia (OR 3.911; 0.994–15.397; p = 0.041) and significantly more often ended with delivery by caesarean section (63.8 % (28/41) vs 28.6 % (10/35); p = 0.001).Conclusions. The increase in the incidence of GDM among patients whose pregnancy occurred as a result of ART is associated with a later reproductive age, initially aggravated obstetric anamnesis and somatic pathology at the time of entry into the ART protocols, as well as long-term hormonal support of pregnancy after the use of ART from early pregnancy.
Keywords: assisted reproductive technologies; pregnancy high-risk; pregnancy complications; pregnancy outcome; gestational diabetes mellitus